Predicting health behaviors with economic preferences and perceived control - Lynn Conell-Price; Julian Jamison (Federal Reserve Bank of Boston, 2012)
We present new evidence on the relationship between health behaviors and experimental measures of risk and time preferences and introduce evidence that perceived control - a measure incorporated from the health psychology literature - is a stronger and more consistent predictor of health behaviors than economic preferences.
Keywords: C91; D03; I12; 330